A meeting of post(s), Is it possible to separate doing of thinking?, Is it possible to separate thinking of doing? - Burgos, Hugo (post(s), 2025)
This article questions the apparent dispute between academic productions based on theory with one based on practice. Walter Benjamin"™s notion of the "author as producer" is used to value in equivalent ways both forms of production. Also, arts based research is proposed as an alternative to positivist research. Finally, this book is presented as a meeting and inscription point of studies that place into dialogue theory with practice.